2004
DOI: 10.1051/0004-6361:20034438
|View full text |Cite
|
Sign up to set email alerts
|

Near-IR speckle imaging of massive young stellar objects

Abstract: Abstract. We present near-IR speckle images of 21 massive Young Stellar Objects (YSOs) associated with outflows. The aim of this study is to search for sub-arcsecond reflection nebulae associated with the outflow cavity. We find that 6 of the massive YSOs show a conical nebula which can be interpreted in terms of reflected light from the dusty walls of the outflow cavity. In all cases, the small scale structures seen in our images are compared with outflow indicators found in the literature. No clear correlati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 110 publications
(183 reference statements)
6
53
1
Order By: Relevance
“…However, although there is some low surface brightness emission at large angular distances from the protostar, the image is dominated by a conical, monopolar nebula whose centre of brightness is offset from the location of the protostar. The angular extent of the conical nebula (about 2 arc seconds) is rather larger than the typical size of those observed by Alvarez et al (2004) at our 1 kpc distance.…”
Section: Imagescontrasting
confidence: 54%
See 1 more Smart Citation
“…However, although there is some low surface brightness emission at large angular distances from the protostar, the image is dominated by a conical, monopolar nebula whose centre of brightness is offset from the location of the protostar. The angular extent of the conical nebula (about 2 arc seconds) is rather larger than the typical size of those observed by Alvarez et al (2004) at our 1 kpc distance.…”
Section: Imagescontrasting
confidence: 54%
“…The longer wavelength images are dominated by cool, dense dust in the disc around the protostar. Alvarez et al (2004) presented H and K band speckle Figure 6. Synthetic spectral energy distributions plotted logarithmically as λF λ against wavelength in microns.…”
Section: Imagesmentioning
confidence: 99%
“…The first K-band speckle images, taken with the 3.5 mtelescope on Calar Alto were presented by Alvarez et al (2004) and showed substructure in the vicinity of IRS1; namely, two strong blobs (A, PA ∼ −45…”
Section: Previous Studies Of Ngc 7538mentioning
confidence: 99%
“…The well known highmass protostellar system AFGL 961 is situated well within this region (Cohen 1973;Grasdalen et al 1983;Castelaz et al 1985;Lenzen et al 1984;Hodapp 1994). The third component of the system, designated AFGL 961 II (Li & Smith 2005), was first noticed to be associated with a small nebulosity by Eiroa (1981) and later briefly discussed by Hodapp (1994) was considered a cavity with a partial shell surrounding the central young star (Aspin 1998;Alvarez et al 2004). However, the origin of the intriguing YSO is far from clear.…”
Section: Introductionmentioning
confidence: 99%